2002
DOI: 10.1046/j.1460-9568.2002.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of linear vestibular and visual stimulation in the macaque ventral intraparietal area (VIP)

Abstract: Navigation in space requires the brain to combine information arising from different sensory modalities with the appropriate motor commands. Sensory information about self-motion in particular is provided by the visual and the vestibular system. The macaque ventral intraparietal area (VIP) has recently been shown to be involved in the processing of self-motion information provided by optical flow, to contain multimodal neurons and to receive input from areas involved in the analysis of vestibular information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 46 publications
(81 reference statements)
6
127
0
1
Order By: Relevance
“…Putative sites mediating the further remapping process include areas within the parietal and the premotor cortex, as well as subcortical areas such as the putamen (Graziano & Gross, 1993). For example, the ventral intraparietal area (VIP) contains neurons representing visual, vestibular, tactile and auditory information (Schlack et al, 2002(Schlack et al, , 2005Bremmer et at., 2001) and responds both to stimuli on the skin and the surrounding peripersonal space (Duhamel, Colby, & Goldberg, 1998). The ventral premotor cortex also contains neurons highly responsive to arm position responding to both touch and visual input in peripersonal space (Graziano, Yap, & Gross, 1994), and together with VIP has been suggested to constitute a multisensory representation of peripersonal space in monkeys (Graziano & Cooke, 2006) and in humans (Lloyd, Shore, Spence, & Calvert, 2003).…”
Section: Perceiving the Location Of Tactile Objects In External Spacementioning
confidence: 99%
“…Putative sites mediating the further remapping process include areas within the parietal and the premotor cortex, as well as subcortical areas such as the putamen (Graziano & Gross, 1993). For example, the ventral intraparietal area (VIP) contains neurons representing visual, vestibular, tactile and auditory information (Schlack et al, 2002(Schlack et al, , 2005Bremmer et at., 2001) and responds both to stimuli on the skin and the surrounding peripersonal space (Duhamel, Colby, & Goldberg, 1998). The ventral premotor cortex also contains neurons highly responsive to arm position responding to both touch and visual input in peripersonal space (Graziano, Yap, & Gross, 1994), and together with VIP has been suggested to constitute a multisensory representation of peripersonal space in monkeys (Graziano & Cooke, 2006) and in humans (Lloyd, Shore, Spence, & Calvert, 2003).…”
Section: Perceiving the Location Of Tactile Objects In External Spacementioning
confidence: 99%
“…Yet, up to now, only few studies have addressed the functional implications. Single cell responses in monkeys and imaging studies in humans have revealed activation by means of visual, vestibular, and somatosensory stimulation (Colby et al, 1993;Duhamel et al, 1998;Bremmer et al, 2001Bremmer et al, , 2002aSuzuki et al, 2001;Schlack et al, 2002). The projections to area VIP summarized by Lewis and Van Essen (2000) showed additionally immense inputs from auditory areas.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, macaque areas VIP and MST share a number of response features. Most importantly, these are visual and vestibular self-motion responses Chen et al 2011b;Duffy 1998;Duffy and Wurtz 1991a;Schlack et al 2002;Takahashi et al 2007). Responses from populations of neurons in both areas allow to decode heading in a fixed gaze condition (Bremmer et al 2002a;Britten 2008;Gu et al 2010;Lappe et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons in area MST respond to visual and vestibular self-motion signals, and their causal role in heading perception has been confirmed Duffy 1998;Duffy andWurtz 1991a, 1991b;Gu et al 2007Gu et al , 2008Gu et al , 2010Gu et al , 2012Lappe et al 1996;Morgan et al 2008;Page and Duffy 2003;Yu et al 2010). Neurons in area VIP respond not only to visual and vestibular but also to tactile and auditory stimulation (Avillac et al 2005(Avillac et al , 2007Ben Hamed et al 2002;Bremmer et al 2002aBremmer et al , 2002bChen et al 2011b;Duhamel et al 1998;Schlack et al 2002). Like for area MST, behavioral experiments have demonstrated a critical role of area VIP for heading perception (Britten 2008;Chen et al 2013;Zhang et al 2004;Zhang and Britten 2011).…”
mentioning
confidence: 96%